ORAL AND DENTAL MANAGEMENT IN CHILDREN WITH TETRALOGY OF FALLOT : A LITERATURE REVIEW - Welly Anggarani; Sandy Christiono; Prima Agusmawanti (ODONTO : Dental Journal, 2021)
Background: Congenital heart disease is a condition of heart anomaly and or disfunction of heart since birth. The most common congenital heart disease is Tetralogy Of Fallot (TOF). The disorder has four features, a ventricular septal defect, aortic overriding, stenosis pulmonary, and hypertrophy right ventricular.Method: This review aimed to talk about oral manifestations and discuss options of several oral and dental management in children with TOF.Result: Oral and dental treatment of pediatric patient with cardiovascular disease is important to be carried out with the risk of bacterial endocarditis.Conclusion: Oral and dental management in a child with congenital heart disease is very important. Main point of dental management are dental health education, preventive dental treatment and control periodic after dental treatment.